Small autochthonous ethnic groups and the multicultural model of civil society - Hermanik, Klaus-Jürgen (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2004)
This paper focuses on the triangle created by Civil Society, Ethnicity and State and their interrelationships. Out of these three aspects, retaining ethnicity is most important for ethnic groups and minorities. It will also present three examples of small ethnic groups in the Alpine-Danube-Adriatic region and each group's place within the triangle of Civil Society, Ethnicity and State. Many of them have become victims of national and ethnocratic movements. In most cases they developed a hiding strategy in order to retain their ethnic identity vis-á-vis tendencies towards assimilation. In different ways they were also confronted with identity management from the outside. By focusing on small ethnic groups and hidden minorities, contexts will be discussed that guide us to a multicultural and multiethnic civil society. I will conclude by discussing the following questions: a) How can a multiethnic model of Civil Society be protected by a differentiated legal framework? b) Which basic political requirements are necessary to stop the assimilation process and guarantee the survival of small ethnic groups?
Keywords: civil society; civilna družba; etnične skupine; multikulturnost; pravna ureditev